Brain imaging studies of emotional well-being: a scoping review - Richter, Caroline G.; Li, Celine Mylx; Turnbull, Adam; Haft, Stephanie L.; Schneider, Deborah; Luo, Jie; Lima, Denise Pinheiro; Lin, Feng Vankee; Davidson, Richard J.; Hoeft, Fumiko (Frontiers in Psychology, 2024)
This scoping review provides an overview of previous empirical studies that used brain imaging techniques to investigate the neural correlates of emotional well-being (EWB).We compiled evidence on this topic into one accessible and usable document as a foundation for future research into the relationship between EWB and the brain. PRISMA 2020 guidelines were followed. We located relevant articles by searching five electronic databases with 95 studies meeting our inclusion criteria. We explored EWB measures, brain imaging modalities, research designs, populations studied, and approaches that are currently in use to characterize and understand EWB across the literature. Of the key concepts related to EWB, the vast majority of studies investigated positive affect, followed by life satisfaction, sense of meaning, goal pursuit, and quality of life. The majority of studies used functional MRI, followed by EEG and event-related potential-based EEG. The neural basis of experienced affect (predominantly positive mood) has been studied significantly more often than evaluative (e.g., life satisfaction, sense of meaning) aspects of EWB. Our findings suggest that future studies should investigate EWB in more diverse samples, especially in children, individuals with clinical disorders, and individuals from various geographic locations. Future directions and theoretical implications are discussed, including the need for more longitudinal studies with ecologically valid measures that incorporate multi-level approaches allowing researchers to better investigate and evaluate the relationships among behavioral, environmental, and neural factors.